(Un) Gendering Bullying in Academic Spaces: The Case of Queer Resistance and Identity Assertion - Colita, Lloyd Anton Von (International Journal of Language and Literary Studies, 2025)
This study examines how queer students in University of Southern Mindanao, Cotabato, experience, negotiate, and resist gendered bullying within academic settings. Using discourse analysis of questionnaires, interviews, and focus group discussions, the research addresses three central questions: the linguistic features of gendered bullying, the strategies queer students use to resist it, and the ideologies that shape both bullying and resistance. Findings show that gendered bullying relies heavily on language, including slurs, religious moralizing, metaphors tied to purity and masculinity, and labels that enforce a rigid gender binary. These linguistic acts reflect broader cultural and religious ideologies that define gender as fixed, morally evaluated, and publicly policed. In response, queer students employ a range of resistance strategies that emphasize both safety and agency. These include silence, off-record language use, humor, code-switching, calm assertion, and deliberate educational dialogue. A significant form of resistance that emerged is excellence-driven resilience: many queer students strategically cultivate academic excellence, leadership, and intellectual competence to assert worth, reclaim dignity, and reduce their vulnerability to bullying. By anchoring their social position in demonstrated merit, they lessen their vulnerability to bullying and neutralize gender as the basis for discriminatory treatment. By combining Butler’s performativity lens with sociolinguistic theory, this study demonstrates how queer students actively negotiate identity, challenge rigid gender norms, and transform academic spaces into arenas of empowerment. The study finds that ideologies shaping bullying are rooted in patriarchal norms, community expectations, and faith-based interpretations that privilege conformity. However, queer students reinterpret these same cultural and religious values to promote empathy, inclusivity, and spiritual resistance. By combining linguistic strategies with academic performance as symbolic capital, they create new forms of identity assertion that challenge traditional norms. A key finding of this study is that queer Cotabateño students navigate the university as a contested space where identity is continuously negotiated through performance, scrutiny, and the pursuit of symbolic capital. By strategically leveraging academic merit, they reshape how others perceive them, resist gendered bullying, and create alternative pathways to recognition. This form of academic-based queer resistance underscores how language, achievement, and personal performance collectively serve as tools of empowerment, enabling students to challenge gendered oppression and redefine belonging in academic settings.